Epidemiology of geographic disparities in heart failure among US older adults: a Medicare-based analysis - Bin Yu; Igor Akushevich; Arseniy P. Yashkin; Anatoliy I. Yashin; H. Kim Lyerly; Julia Kravchenko (BMC, 2022)
Abstract Background There are prominent geographic disparities in the life expectancy (LE) of older US adults between the states with the highest (leading states) and lowest (lagging states) LE and their causes remain poorly understood. Heart failure (HF) has been proposed as a major contributor to these disparities. This study aims to investigate geographic disparities in HF outcomes between the leading and lagging states. Methods The study was a secondary data analysis of HF outcomes in older US adults aged 65+, using Center for Disease Control and Prevention sponsored Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) database and a nationally representative 5% sample of Medicare beneficiaries over 2000-2017. Empiric estimates of death certificate-based mortality from HF as underlying cause of death (CBM-UCD)/multiple cause of death (CBM-MCD); HF incidence-based mortality (IBM); HF incidence, prevalence, and survival were compared between the leading and lagging states. Cox regression was used to investigate the effect of residence in the lagging states on HF incidence and survival. Results Between 2000 and 2017, HF mortality rates (per 100,000) were higher in the lagging states (CBM-UCD: 188.5-248.6; CBM-MCD: 749.4-965.9; IBM: 2656.0-2978.4) than that in the leading states (CBM-UCD: 79.4-95.6; CBM-MCD: 441.4-574.1; IBM: 1839.5-2138.1). Compared to their leading counterparts, lagging states had higher HF incidence (2.9-3.9% vs. 2.2-2.9%), prevalence (15.6-17.2% vs. 11.3-13.0%), and pre-existing prevalence at age 65 (5.3-7.3% vs. 2.8-4.1%). The most recent rates of one- (77.1% vs. 80.4%), three- (59.0% vs. 60.7%) and five-year (45.8% vs. 49.8%) survival were lower in the lagging states. A greater risk of HF incidence (Adjusted Hazards Ratio, AHR [95%CI]: 1.29 [1.29-1.30]) and death after HF diagnosis (AHR: 1.12 [1.11-1.13]) was observed for populations in the lagging states. The study also observed recent increases in CBMs and HF incidence, and declines in HF prevalence, prevalence at age 65 and survival with a decade-long plateau stage in IBM in both leading and lagging states. Conclusion There are substantial geographic disparities in HF mortality, incidence, prevalence, and survival across the U.S.: HF incidence, prevalence at age 65 (age of Medicare enrollment), and survival of patients with HF contributed most to these disparities. The geographic disparities and the recent increase in incidence and decline in survival underscore the importance of HF prevention strategies.